Binding of the cyclic AMP receptor protein of Escherichia coli and DNA bending at the P4 promoter of pBR322. - Brierley, I (1992)
The binding of the Escherichia coli cyclic AMP receptor protein (CRP) to its specific site on the P4 promoter of pBR322 has been studied by gel electrophoresis. Binding to the P4 site was about 40-50-fold weaker than to the principal CRP site on the lactose promoter at both low (0.01 M) and high (0.1 M) ionic strengths. CRP-induced bending at the P4 site was investigated from the mobilities of CRP bound to circularly permuted P4 fragments. The estimated bending angle, based on comparison with Zinkel & Crothers [(1990) Biopolymers 29, 29-38] A-tract bending standards, was found to be approximately 96 degrees, similar to that found for binding to the lac site. These observations suggest that there is not a simple relationship between strength of CRP binding and the extent of induced bending for different CRP sites. The apparent centre of bending in P4 is displaced about 6-8 bp away from the conserved TGTGA sequence and the P4 transcription start site.